2013
DOI: 10.1089/scd.2012.0584
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Isolation of Mesenchymal Stem Cells from Human Bone Marrow Using Novel Antibodies Directed Against Sushi Domain Containing 2

Abstract: Several strategies have been developed to facilitate the prospective isolation of bone marrow-derived mesenchymal stem/stromal cells (BM-MSCs) based on the selective expression or absence of surface markers. Recently, we described the monoclonal antibodies W3D5 and W5C5, which selectively react with BM-MSCs, but not with hematopoietic cells. Both antibodies showed an identical reactivity pattern, indicating that they may recognize the same molecule. To identify the cognate antigen, cultured MSCs were sorted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 50 publications
3
57
0
Order By: Relevance
“…W5C5 could be used as a novel marker for the prospective isolation of endometrial MSCs from biopsy, curettage, or hysterectomy tissue. In addition, W5C5 expressed with high selectivity on human bone marrow-derived MSCs [3]. In the present study, W5C5 was identified as a novel single marker for purifying T-MSCs, which self-renew and differentiate into adipogenic, osteogenic, and chondrogenic cell lineages.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…W5C5 could be used as a novel marker for the prospective isolation of endometrial MSCs from biopsy, curettage, or hysterectomy tissue. In addition, W5C5 expressed with high selectivity on human bone marrow-derived MSCs [3]. In the present study, W5C5 was identified as a novel single marker for purifying T-MSCs, which self-renew and differentiate into adipogenic, osteogenic, and chondrogenic cell lineages.…”
Section: Discussionmentioning
confidence: 59%
“…W5C5, a known epitope of the sushi domain containing two (SUSD2) molecules, was recently identified as the transmembrane protein of 820 amino acids consisting of a large extracellular region containing a Somatomedin B, an adhesion-associated domain in MUC4 and other proteins, a von Willebrand factor, and a Sushi domain [3]. Sushi domains are components of a variety of complement and adhesion proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these antigens, expression of the stage-specific embryonic antigen 4 (SSEA-4) or fibroblast activation protein-a (FAPA) were suggested as marker antigens for MSC [7,8]. However, other antigens such as CD146 (alias MCAM, MUC18), the sushi-containing domain 2 protein (susd2, alias W5C5 antigen) [9], or the molecule detectable by monoclonal antibody clone W12D1 (protein unknown) generated distinct histogram patterns, indicating that MSC prepared by conventional techniques present a complex mixture of cells [10,11].…”
mentioning
confidence: 99%